Long noncoding RNA antisense noncoding RNA in the INK4 locus inhibition alleviates airway remodeling in asthma through the regulation of the microRNA‐7‐5p/early growth response factor 3 axis - Liyan Wang; Xueru Liu (Immunity, Inflammation and Disease)
Abstract Asthma, a chronic inflammatory disease of the airways, clinically manifests as airway remodeling. The purpose of this study was to probe the potential role of long noncoding RNA (lncRNA) antisense noncoding RNA in the INK4 locus (lncRNA ANRIL) in the proliferation and migration of airway smooth muscle cell (ASMC) and to explore its potential mechanisms in asthma. Serum samples were obtained from 30 healthy volunteers and 30 patients with asthma. Additionally, platelet‐derived growth factor‐BB (PDGF‐BB) was used to induce airway remodeling in ASMCs. The level of lncRNA ANRIL and microRNA (miR)‐7‐5p in serum samples were measured by quantitative reverse transcriptase polymerase chain reaction (qRT‐PCR). TargetScan predicted the binding site of miR‐7‐5p to early growth response factor 3 (EGR3) and validated the results using a dual‐luciferase reporter assay. 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyl‐2H‐tetrazolium bromide (MTT) and Transwell assays were used to detect cellular proliferation and migration, respectively. Subsequently, changes in proliferation‐ and migration‐related genes were verified using western blot analysis and qRT‐PCR. These results indicate that lncRNA ANRIL was upregulated in the serum and PDGF‐BB‐induced ASMCs of patients with asthma, whereas miR‐7‐5p expression was reduced. EGR3 was a direct target of miR‐7‐5p. LncRNA ANRIL silencing inhibited the proliferation or migration of ASMCs induced by PDGF‐BB through miR‐7‐5p upregulation. Mechanistic studies indicated that miR‐7‐5p inhibits the proliferation or migration of PDGF‐BB‐induced ASMCs by decreasing EGR3 expression. EGR3 upregulation reverses the role of miR‐7‐5p in airway remodeling. Thus, downregulation of lncRNA ANRIL inhibits airway remodeling through inhibiting the proliferation and migration of PDGF‐BB‐induced ASMCs by regulating miR‐7‐5p/EGR3 signaling.